ANALYSIS OF THE USE OF CLAIMED AND TRADITIONAL SPLINTING ORTHOPEDIC STRUCTURES IN PATIENTS WITH GENERALIZED PERIODONTITIS DURING STABILIZATION STAGE WHO HAVE DENTITION DEFECT IN TERMS OF BONE AREA DESTRUCTION FACTOR - P. V. Ishchenko; A. V. Borisenko (Eastern Ukrainian Medical Journal, 2019)
Introduction. Periodontal pathology accounts for many dental diseases, which encourages dentists and scientists to engage in this problem more actively. For the treatment of generalized periodontitis by the orthopedic component, we have proposed the claimed interdental splints, which were used in the orthopedic treatment of patients with this pathology in addition to the traditional ones. Defects in the lateral areas were recovered with the help of bridge structures. Purpose. To find out which of the splints used in the study are more physiological for the provoked parodontium in their area of ​​responsibility using the bone area destruction factor. Materials and Methods. This clinical study was conducted in a group of 60 patients with generalized periodontitis in stabilization stage. Previously, they had undergone comprehensive treatment for generalized periodontitis. 30 subjects were included into the study group with periodontal condition in stabilization stage – the group with the declared tested splints. And the group with known traditional splints included 30 subjects. Results. The study found that after 18 months, the bone area destruction indicator decreased in patients with dentition defects where splints and bridges were used in the control group as compared to the value 6 months after treatment, by an average of 7.0 ± 1,1%, and it was only 2.9 ± 0.1% (p < 0.001) in the study group. Conclusions. During the whole period of the study in the group with dentition defects, the dynamics of restraining the increase in bone destruction in the study group is more obvious as compared to the control group. This indicates the feasibility of applying the claimed structures in this group of patients. The improvement in the percentage ratio was 4.1 ± 1.1% in 18 months.